The 21st-century Character of a Village Main Square: Revitalization of Tisza István Square, Nagykovácsi - Almási, Balázs; Bakay, Eszter; Balogh, Péter István; Gergely, Antal (4D Journal of Landscape Architecture and Garden Art, 2010)
The article discusses the 21st-century revitalization of Tisza István Square in Nagykovácsi, highlighting the preservation of the village’s identity and the strengthening of its community functions. It analyzes the landscape architectural challenges faced by settlements in the Budapest agglomeration, where villages are developing new identities, distancing themselves from the urban character of the capital. Nagykovácsi’s main square, which previously served primarily as a transportation hub, has been transformed into a community space through planned renovations. The aim of the redesign was to provide space for public events, increase the proportion of green areas, and strengthen the sense of identity among local residents. As part of the project, the traffic system was restructured to reduce vehicular traffic and create more pedestrian-friendly solutions. The renovation focused on preserving historical traditions while meeting modern expectations, ensuring that the square becomes a livable and enjoyable space for both locals and visitors.